PERLINDUNGAN TERHADAP ANAK KORBAN PELECEHAN SEKSUAL DENGAN MODUS TRANSFORMASI SEKSUAL TERHADAP ANAK (STUDI KASUS DI KABUPATEN CIANJUR) - Trini Handayani; Henny Nuraeny (Jurnal MHKI, 2022)
This study discusses efforts to protect children who have been victims of sexual abuse with the modus operandi of sexual transformation in Cianjur Regency. The purpose of this study is to determine the protective measures taken by relevant parties and the factors that influence the success of protection. The method used is descriptive qualitative with data collection techniques in the form of in-depth interviews and participatory observation. The study subjects include child victims, families, police, courts, and child protection agencies. The results show that protection for children who are victims of sexual abuse with the modus operandi of sexual transformation is still less than optimal due to factors such as lack of public knowledge, insufficient trained personnel, lack of support from families and society, as well as administrative and legal issues. Therefore, serious and integrated efforts are needed to protect children who are victims of sexual abuse with the modus operandi of sexual transformation by increasing public knowledge, training relevant personnel, providing moral and psychological support, and evaluating existing policies and regulations.